Basics of qualitative research techniques and procedures for developing grounded theory. - Corbin, Juliet M., 1942- (SAGE, 2008)
This edition takes the form of an informal dialogue, akin to students and teachers working together in a classroom. It shows the evolution of grounded theory method over time and the influence of constructionists and post-modern trends.